Changes in cortisol levels by continuous positive airway pressure in patients with obstructive sleep apnoea: Meta‐analysis of 637 individuals. (6th August 2021) - Ken‐Dror, Gie; Fry, Christopher H.; Murray, Paul; Fluck, David; Han, Thang S.
Abstract: Background: Obesity, obstructive sleep apnoea (OSA) and hypertension frequently coexist and are associated with elevated cortisol levels. Identification and treatment of such patients is important when investigating for suspected Cushing's syndrome and hypertension. Studies of the impact of continuous positive airway pressure (CPAP) on cortisol and blood pressure are limited by the small sample size and show conflicting findings. We conducted a meta‐analysis to document changes in the levels of cortisol and blood pressure in response to CPAP treatment of OSA. Methods: Meta‐analysis was conducted using RevMan (v5.3) and expressed in standardized mean difference (SMD) for catecholamines and mean difference for systolic (SBP) and diastolic blood pressure (DBP). The quality of the studies was evaluated using standard tools for assessing the risk of bias. Results: A total of 22 studies met our search criteria; they consisted of 16 prospective cohort studies (PCS) that recruited 385 participants and six randomized control trials (RCT) totalling 252 participants. The range of mean age was 41–62 years and BMI 27.2–35.1 kg/m 2 . CPAP treatment reduced plasma cortisol levels in PCS: SMD = −0.28 [95% confidence interval (95% CI) = −0.45 to −0.12], I 2  = 0%, p  = .79 and in RCT: SMD = −0.39 (95% CI = −0.75 to −0.03), I 2  = 28.3%, p  = .25. CPAP treatment reduced SBP by 5.4 mmHg (95% CI = 1.7–9.1) and DBP by 3.3 mmHg (95% CI = 1.0–5.7). Interstudy heterogeneity was low for all studies. Bias in most RCT arose from the lack of blinding of participants and personnel. Conclusion: CPAP treatment in individuals with OSA reduces cortisol levels and blood pressure.